(untitled) (Revista de Ciências Agroveterinárias, 2015)
The purpose of this study was to time analyze the series of temperature and precipitation in the period from 1961 to 2011 from the EPAGRI/CIRAM weather station records located in Lages-SC, Brazil. The corrections of failures were made up of readings from the regional weighting method, and a proposed alternative model of linear regression with lowest MSE. The methods of Fourier Transform, Wavelet Transform and statistical test of Mann-Kendall were used. The presence of annual cycles for the mean monthly temperature and cycles ranging from 3 to 5 years for monthly accumulated precipitation were detected. There is a positive trend in the pattern of monthly cumulative rainfall from the El Niño of 1983, according to the Mann-Kendall test, and in minimum and maximum temperatures in some months of both absolute and relative to the monthly average.